2016
DOI: 10.1038/srep26220
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a GnRH receptor agonist, but not the GnRH receptor antagonist degarelix, induces atherosclerotic plaque instability in ApoE−/− mice

Abstract: Androgen-deprivation therapy (ADT) for prostate cancer has been associated with increased risk for development of cardiovascular events and recent pooled analyses of randomized intervention trials suggest that this primarily is the case for patients with pre-existing cardiovascular disease treated with gonadotropin-releasing hormone receptor (GnRH-R) agonists. In the present study we investigated the effects of the GnRH-R agonist leuprolide and the GnRH-R antagonist degarelix on established atherosclerotic pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 30 publications
2
41
1
Order By: Relevance
“…Data taken from Nguyen et al (19) and Bosco et al (12) . that acute ADT promotes inflammation, atherosclerosis and destabilises plaque (16) , and that this relates specifically to GnRH agonists and not antagonists. A comparison between the components of classic MetS and ADT-induced cardiometabolic risk factors is shown in Table 1.…”
Section: Nutrition Research Reviewsmentioning
confidence: 96%
See 1 more Smart Citation
“…Data taken from Nguyen et al (19) and Bosco et al (12) . that acute ADT promotes inflammation, atherosclerosis and destabilises plaque (16) , and that this relates specifically to GnRH agonists and not antagonists. A comparison between the components of classic MetS and ADT-induced cardiometabolic risk factors is shown in Table 1.…”
Section: Nutrition Research Reviewsmentioning
confidence: 96%
“…These findings were soon corroborated by further primary studies, and a highly publicised metaanalysis of observational prospective cohort studies that showed GnRH agonists to be associated, unequivocally, with an increased risk of fatal and non-fatal CVD (12) . These associations have been linked to the adverse effects of ADT on body composition, insulin sensitivity and other cardiometabolic risk factors described below (6) , and also to the specific effects of GnRH agonists in precipitating cardiac events by promoting vascular dysfunction (13)(14)(15) and destabilising atherosclerotic plaque (16) . Nevertheless, RCT have generally failed to substantiate a direct, and thus causal, link between ADT/GnRH agonists and cardiac mortality (17)(18)(19)(20)(21) (Fig.…”
mentioning
confidence: 99%
“…Compared with GnRH agonists in preclinical mouse models, GnRH antagonists were associated with less adiposity, and fewer characteristics of metabolic syndrome and atherosclerosis 55,56 . The effects of GnRH antagonists on glucose control and body composition have yet to be reported in human clinical trials 27 …”
Section: Safetymentioning
confidence: 99%
“…[68,69] A mouse model of ApoE −/− fed a high-fat diet to induce carotid artery atherosclerosis noted that 4 weeks of LHRH agonist therapy was associated with an increase in the plaque necrosis and macrophage infiltration, theoretically making such plaques more susceptible to rupture, while treatment with degarelix was not associated with this histologic change. [70] Another possible biologic explanation may lie in the presence of FSH receptors within the endothelial surface of blood vessels. FSH receptors that would be stimulated by LHRH agonist therapy but would presumably be less stimulated through GnRH antagonist therapy which also suppresses FSH.…”
Section: Cardiovascular Effects Of Gnrh Antagonistsmentioning
confidence: 99%